The Effect Of Kimpul Taro Flour (Xanthosoma Sagittifolium) Substitution On The Physical And Sensory Quality Of Onde-Onde - Dinda Fitria Bintang; Cucu Cahyana; Guspri Devi Artanti (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study investigated the effect of substituting kimpul taro flour (Xanthosoma sagittifolium) for other flours on the physical and sensory quality of onde-onde, as a local food diversification strategy. An experimental method was applied using 10%, 20%, and 30% kimpul taro flour substitution for glutinous rice flour. A non-substituted formulation was used as the control in the physical quality tests. Physical quality was evaluated by measuring surface oil retention and changes in oil volume after frying, with three replications, and the data were analyzed using analysis of variance at the 5% significance level. Sensory quality was evaluated by 45 semi-trained panelists, with 15 panelists assigned to each treatment, covering color, kimpul taro aroma, sweetness, kimpul taro taste, texture, and overall appearance. Sensory data were analyzed using the Kruskal-Wallis test. The results showed that 10-30% substitution did not significantly affect surface oil retention or changes in oil volume. None of the sensory attributes differed significantly because all calculated chi-square values were lower than the critical value. Descriptively, the 10% treatment produced mean scores of 4.7 for color, 4.5 for sweetness, and 4.4 for texture, and most closely resembled the standard product. Substitution up to 30% remained acceptable in sensory terms, although higher substitution levels tended to reduce color brightness and chewiness. Kimpul taro flour can therefore be used as a partial substitute in onde-onde, with the 10% level recommended as the most stable formulation based on the combined physical and sensory results.